Proposing a Novel Adaptive Learning Management System: An Application of Behavior Mining & Intelligent Agents. Issue 2 (3rd April 2017) - Oskouei, Rozita Jamili; Kor, Nasroallah Moradi
Abstract: Nowadays, the internet has become one of the main resources for distance education, learning or training purposes. Various learning management systems (LMSs) have been designed for providing various services to learners in all parts of the world. Each of these LMSs has some similarities or differences with others regarding to capabilities or services. One of the main problems in Iran is teaching foreign languages to people with different genders, experiences, jobs, educational levels, etc. People need to learn English for different purposes, but unfortunatly, all the learning matrials are similar for all the learners without considering their capabilities, age, actual usage, etc. This paper attempts to design a personalized LMS for teaching foreign language to people whose native language is not English. Our experimental results indicated that the proposed LMS is useful for teaching conversation or grammar of foreign languages such as English language even to illiterate people or those with low education. Furthermore, the proposed LMS decreased the time of learning process and increased the duration of remembering the words or grammar.